Communication outside the media is a bet for drawing a tourism communication strategy for the Territorial field Tourism Directorate Souk Ahras is a model - araibia, mohamed karim; zemmour, bader eddin (Journal of Social Sciences and Humanities, 2023)
The abstract should consist of a single paragraph. It should be a summary of the paper and not an introduction. Because the abstract may be used in abstracting and indexing databases, it should be self-contained (i.e., no numerical references) and substantive in nature, presenting concisely the objectives, methodology used, results obtained, and their significance.